Marketing Strategy of Brokerage Business of Shanxi Securities Company, China - Li, Rongwei; Prompanyo, Manoch; Srichum, Somporn; Sansuk, Tananrat (วารสารวิทยาการจัดการและการบัญชี, 2022)
Research objectives were to explore the industry competition environment that Shanxi Securities Company (SSC) faced in developing brokerage business. Defined the Company’s competitive advantages marketing strategy by TOWS Matrix. Result found: marketing status: Product and Quotation Strategy; Customer Relationship Management Strategy; Marketing Channel Strategy. The Problems Existing in the Marketing: Vague Product Positioning; Low Customer Willingness to Pay; Low Brand Awareness; Customers were not satisfied with service staffs. The Analysis on the Causes of the Marketing Problems in the Brokerage Business: Lack of Scientific Product Analysis System; Single Product Quotation; High-level Neglect of Online Channel Construction.